Early detection of infant hearing impairment - Titirungruang, C.; Charusripan, P.; Patarapak, S. (Chulalongkorn Medical Journal, 2023)
Hearing loss in children is one of the important healthcare problems. Early detection and prompt rehabilitation improve their language and other developments. The hearing of infants should be screened at no later than 1 month of age. Those who do not pass the screening should be confirmed of hearing loss at no later than 3 months of age. The infants who are confirmed hearing loss should receive aural rehabilitation at no later than 6 months of age. The physiologic measurement of newborn and infant hearing loss includes automated evoked otoacoustic emission (EOAE) and automated auditory brainstem response (ABR), usually used as the screening tools. For confirmation of hearing loss, battery tests of audiological evaluations include diagnostic EOAE, diagnostic ABR and tympanometry should be done. Moreover, the children should receive medical evaluation in order to find the cause of hearing loss. Auditory skill surveillance should be done in all infants at age 9, 18, 24 - 30 months or if there is parental concern of hearing loss, especially in children with risk indicators should be referred for audiological assessment at least once within 24 - 30 months of age because some children develop hearing loss or progressive hearing loss later. Children with hearing loss should receive early hearing rehabilitation such as hearing aids, implantable hearing devices or cochlear implantation. However, many hospitals in Thailand cannot follow the guidelines because of limitation of audiologists, screening tools and hearing devices, so each institute should adjust the guideline to suit to their situations.